2017
DOI: 10.1371/journal.pgen.1006675
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of Tibetans inferred from whole-genome sequencing

Abstract: The indigenous people of the Tibetan Plateau have been the subject of much recent interest because of their unique genetic adaptations to high altitude. Recent studies have demonstrated that the Tibetan EPAS1 haplotype is involved in high altitude-adaptation and originated in an archaic Denisovan-related population. We sequenced the whole-genomes of 27 Tibetans and conducted analyses to infer a detailed history of demography and natural selection of this population. We detected evidence of population structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
86
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 72 publications
7
86
1
Order By: Relevance
“…Their permanent settlement in the Qinghai-Tibetan plateau was dated as early as 30,000 years ago based on genetic data (Shi, et al 2008;Qi, et al 2013;Lu, et al 2016). Previous genetic studies have identified two key genes (EPAS1 and EGLN1) carrying adaptive alleles that help maintain relatively lower hemoglobin concentration in native Tibetans so that over-production of red cells (polycythemia) at high altitude could be avoided [7][8][9][10][11][12][13][14][15][16][17] . Also, a Tibetanenriched 3.4kb deletion (TED) near EPAS1 was reported 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their permanent settlement in the Qinghai-Tibetan plateau was dated as early as 30,000 years ago based on genetic data (Shi, et al 2008;Qi, et al 2013;Lu, et al 2016). Previous genetic studies have identified two key genes (EPAS1 and EGLN1) carrying adaptive alleles that help maintain relatively lower hemoglobin concentration in native Tibetans so that over-production of red cells (polycythemia) at high altitude could be avoided [7][8][9][10][11][12][13][14][15][16][17] . Also, a Tibetanenriched 3.4kb deletion (TED) near EPAS1 was reported 18 .…”
Section: Introductionmentioning
confidence: 99%
“…module. Then15 we used Picard to mask the PCR duplicates and generated the dedup.bam file. Variants were called by the…”
mentioning
confidence: 99%
“…Over evolutionary time, aerobic organisms have developed sophisticated cellular mechanisms that sense and respond to O 2 gradients, as well as physiological systems that adapt to changes in these gradients (1)(2)(3)(4)(5)(6). As consistent oxygen supply affects evolution, studies of hypoxia adaptation (chronic hypoxia) are common (5,7,8). However, organisms often encounter acute hypoxic conditions in addition to chronic hypoxia (5,(7)(8)(9), yet organis-mal mechanisms of adaptation to chronic hypoxia (i.e.…”
mentioning
confidence: 99%
“…As consistent oxygen supply affects evolution, studies of hypoxia adaptation (chronic hypoxia) are common (5,7,8). However, organisms often encounter acute hypoxic conditions in addition to chronic hypoxia (5,(7)(8)(9), yet organis-mal mechanisms of adaptation to chronic hypoxia (i.e. hypoxia tolerance) remain largely unknown.…”
mentioning
confidence: 99%
“…While some of these genes are known to work in specific pathways, the function of many of these genes is not known. In addition, genome wide association studies have identified variants in a number of genes that may facilitate adaptation to high altitude (Zimmerman et al, 1991;Semenza and Wang, 1992;Melillo et al, 1995;Tuder et al, 1995;Lau et al, 1997;Zaobornyj et al, 2009;Simonson et al, 2010;Hu et al, 2017). This may be of relevance especially in light of the known negative feed-back loop, which results in downregulation of HIF1a mRNA with prolonged hypoxia exposure (Ginouves et al, 2008).…”
Section: Cardiovascular Physiologic Changes After Altitude Exposurementioning
confidence: 99%